2018
DOI: 10.1039/c8cp04516j
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the metals and ligands in dinuclear complexes on phosphopeptide sequencing by electron-transfer dissociation tandem mass spectrometry

Abstract: Phosphorylation is one of the most important protein modification, and electron transfer dissociation tandem mass spectrometry (ETD-MS/MS) is a potentially useful method for sequencing of phosphopeptide, including determination of phosphorylation site. Notably, ETD-MS/MS typically provide useful information when precursor contains more than three positive charges and has not yet closed as the method for large-scale phosphopeptide analysis, due to the difficulty of the production for acidic phopeptides having m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The fluorescence intensity decreased in the presence of Phos-tag acrylamide coordinated to metal ions upon introducing the elution buffer. The ability of Phos-tag to capture phosphorylated compounds differs depending on the phosphorylation site and molecular weight [ 33 ]. When Cu 2+ was used for coordination, the fluorescence intensity was found to be unstable.…”
Section: Resultsmentioning
confidence: 99%
“…The fluorescence intensity decreased in the presence of Phos-tag acrylamide coordinated to metal ions upon introducing the elution buffer. The ability of Phos-tag to capture phosphorylated compounds differs depending on the phosphorylation site and molecular weight [ 33 ]. When Cu 2+ was used for coordination, the fluorescence intensity was found to be unstable.…”
Section: Resultsmentioning
confidence: 99%
“…24 Europium-bound biomolecules and some other heavy metal adducts are also believed to be so-called "electron sinks" and quench electrons. 25 26,27 Despite the partial quenching of ECD electrons by iridium, low intensity fragments were observed in all ECD MS/MS spectra of Ir-containing reaction products (Figure 3+4, SI Figures SF5, SF7, SF15, and SF17. These fragments are summarised in the corresponding fragmentation maps (Figure 3, SF6, SF7, SF13, SF15, and SF17) and SI Tables ST2, ST3, ST4, ST8, ST10, and ST12).…”
Section: Tandem Ms Of Iridium-modified Speciesmentioning
confidence: 98%
“…However, although unsymmetrical 2,6-disubstituted pyridines are widespread building blocks in many fields of chemistry, there is a lack of efficient synthetic strategies when one of these substituents is an amino group. This has been a limitation in the preparative scale production of the intermediates for making metal ion chelating ligands that contain the 2-aminopicolyl structure, despite the favourable impact that these have on binding and reactivity [12][13][14][15][16][17][18][19][20]. The most common previous strategies have focused on the functionalisation of a methyl group in 2-methyl-6-amino-pyridine, after the amino group has been protected.…”
Section: Synthesismentioning
confidence: 99%
“…One group of metal chelating ligands which has been described in the literature for a variety of purposes is the N,N-bis(2-picolyl)amine head group. Metal ion complexes of these tridentate ligands have found applications in molecular imaging, phosphate binding and phosphodiester cleavage [12][13][14][15][16][17]. Of particular relevance to developing artificial nucleases, it has been shown that by modifying the second coordination sphere of the metal ion with 6-amino substituents on the pyridyl ring provides considerably enhanced activity towards phosphate diester cleavage over the parent pyridyl group [18][19][20].…”
Section: Introductionmentioning
confidence: 99%